Peran Upskilling dan Reskilling dalam Pengembangan Sumber Daya Manusia: Analisis Bibliometrik - Fatin Fadila; Muhammad Sholahudin (Sains: Jurnal Manajemen dan Bisnis, 2026)
Digital transformation and the rapid advancement of artificial intelligence have intensified the need for upskilling and reskilling in human resource development (HRD). This study aims to map the global research landscape on upskilling and reskilling by identifying publication trends, key contributors, and dominant research themes using a bibliometric approach. Data were collected from the Scopus database and analyzed using Biblioshiny (R-package Bibliometrix) following the PRISMA protocol. A total of 857 articles were examined to explore annual publication growth, influential authors and countries, and thematic structures. The findings reveal a sharp increase in publications since 2020, with dominant themes including digital transformation, artificial intelligence, and lifelong learning. However, research contributions remain concentrated in developed countries, indicating gaps in developing regions. This study proposes a conceptual framework highlighting the strategic role of upskilling and reskilling in fostering adaptive and sustainable human capital in the era of Industry 5.0.